2004
DOI: 10.1016/s1474-6670(17)31853-0
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Biological Systems Content into the Process Dynamics and Control Curriculum

Abstract: The evolution of the chemical engineering discipline motivates a reevaluation of the process dynamics and control curriculum. A key requirement of future courses is the introduction of theoretical concepts and application examples relevant to emerging areas such as complex biological systems. We outline the critical concepts required to integrate biological content within the traditional framework of process dynamics and control. Our initial experience with three courses is outlined to demonstrate alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…While textbook revisions provide a structured means of renovating PD&C courses , some instructors, such as Gray [15] , Parker [16] , Doyle [16,17] , and Henson [16] , have developed new courses in PD&C that combine biological systems with traditional PD&C topics. The addition of these topics requires the elimination of some of the traditional content, but these investigators have found the addition to be beneficial in enhancing student learning.…”
Section: Recent Pedagogical Advances In Pdandcmentioning
confidence: 99%
“…While textbook revisions provide a structured means of renovating PD&C courses , some instructors, such as Gray [15] , Parker [16] , Doyle [16,17] , and Henson [16] , have developed new courses in PD&C that combine biological systems with traditional PD&C topics. The addition of these topics requires the elimination of some of the traditional content, but these investigators have found the addition to be beneficial in enhancing student learning.…”
Section: Recent Pedagogical Advances In Pdandcmentioning
confidence: 99%